Improving Legal Understanding of Notary Accountability in Authentic Deed Forgery in Malang City : Peningkatan Pemahaman Hukum tentang Tanggung Jawab Notaris dalam Pemalsuan Akta Otentik di Kota Malang - Tongat (Jurnal Dedikasi Hukum, 2025)
Authentic Deed forgery is one of the crimes that often occurs in notarial practice in Indonesia, which can harm the public and the reputation of the notarial profession. This phenomenon is also experienced by the city of Malang, leading to the perception in Malang that the higher the demand for notary services, the greater the opportunity for abuse of authority. The objective of this public legal education programme is to raise legal awareness regarding the responsibilities of notaries in the forgery of authentic deeds through legal socialisation, interactive dialogue, and legal analysis training in the form of case studies, all of which are conducted at the Malang Police Headquarters. The approach applied is educational, participatory, and normative, with notaries, police, and the community as the subjects and beneficiaries of the programme. Through this legal service, there has been an increase in understanding of the role of notaries and categories of legal liability (criminal, civil, and administrative) as well as the elements of the crime of document forgery. Feedback from the assessment shows that participants fully utilised the programme, identified the forms of notary responsibility, and conducted practical analyses of the elements of document forgery. Therefore, this type of legal service is carried out not only as a process of legal socialisation, but also as a means of realising sustainable legal empowerment for the sake of community-oriented justice in the city of Malang.   Abstrak Pemalsuan akta notaris merupakan salah satu kejahatan yang sering terjadi dalam praktik notaris di Indonesia yang dapat merugikan masyarakat dan nama baik profesi notaris. Fenomena ini juga dialami oleh Kota Malang, yang menyebabkan anggapan di Kota Malang bahwa semakin tinggi permintaan akan layanan notaris, semakin besar peluang penyalahgunaan wewenang. Tujuan pendidikan hukum masyarakat ini adalah untuk meningkatkan kesadaran hukum mengenai tanggung jawab notaris dalam pemalsuan akta otentik melalui sosialisasi hukum, dialog interaktif, serta pelatihan analisis hukum dalam bentuk analisis kasus, yang semuanya dilaksanakan di Polresta Malang. Pendekatan yang diterapkan bersifat edukatif, partisipatif, dan normatif, dengan notaris, polisi, dan masyarakat sebagai subjek dan penerima manfaat program. Melalui pengabdian hukum ini, telah menunjukkan peningkatan dalam pemahaman peran notaris dan kategori pertanggungjawaban hukum (pidana, perdata, dan administratif) serta unsur-unsur tindak pidana pemalsua surat. Umpan balik penilaian menunjukkan bahwa peserta sepenuhnya memanfaatkan program, mengidentifikasi bentuk pertanggungjawaban notaris, dan menganalisis secara praktis terkait unsur-unsur tindak pidana pemalsuan surat. Oleh karena itu, pengabdian hukum semacam ini dilaksanakan tidak hanya sebagai proses sosialisasi hukum, tetapi juga sebagai cara untuk mewujudkan pemberdayaan hukum yang berkelanjutan demi keadilan yang berorientasi pada masyarakat di Kota Malang.